UPAYA KOREA SELATAN DALAM MANAJEMEN SAMPAH PASCA KEBIJAKAN NATIONAL SWORD POLICY TIONGKOK TAHUN 2018-2021 (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
China implemented a policy of limiting the import of recycled waste, namely the National Sword Policy in 2018. This policy has an impact on waste issues globally. South Korea is one of the countries that get the impact of China's National Sword Policy implementation, South Korea is experiencing a build-up of domestic waste. South Korea's efforts in waste management after China's 2018-2021 National Sword Policy are explained using the concepts of Waste Management, Environmental Governance, and Environmental Policy. Based on the applied concept, some findings appeared that South Korea made some efforts to solved the problem of domestic waste by improving the waste management system. In improving the waste management system, South Korea made efforts to collaborate on environmental management with parties related to waste. The improvement of the waste management system is manifested in the amendment of the environmental policy regarding waste. This research applies exploratory qualitative method. Keywords: South Korea, Waste Management, Environmental Policy, National Sword Policy.